Experimental Investigation of Compound Effect of Flexural and Torsion on Fiber-Reinforced Concrete Beams - Nabeel H. Al-Salim; Muna H. Jaber; Rafea F. Hassan; Nisreen S. Mohammed; Husam H. Hussein (Buildings, 2023)
Fiber-reinforced concrete is widely acknowledged for its ability to resist cracking effectively and limit its propagation. By preventing cracks from spreading, the addition of fiber composites to concrete can enhance its extensibility and tensile strength, not only at the initial point of cracking but also at its maximum capacity. Additionally, the fibers in fiber-reinforced concrete are capable of binding the matrix, even when exposed to significant cracking. However, there is limited information available about the behavior of fiber-reinforced concrete under a bending moment combined with torsion. This study aims to investigate the structural behavior of fiber-reinforced concrete members subjected to a bending moment with a torsion to moment ratio equal to 1. Synthetic and steel fibers of 1.0% content with different lengths (19, 35, and 55 mm for synthetic fiber and 13 mm for straight and hook steel fibers) were mixed with concrete mixtures to examine the effects of fiber lengths and types on the concrete beam performance. Test results indicated that the fiber-reinforced concrete beams showed higher cracking moments than the normal-strength concrete beam. The steel fiber with a hooked configuration reinforced beam showed increased moment capacity and total torsional toughness higher than that of the straight steel fiber-reinforced beam. The synthetic fiber of a 55 mm length reinforced beam exhibited the highest first-crack and ultimate moment values among other tested beams. The test results were compared with past research models for the moment capacity of beams under the compound effect of bending and torsion and we modified these values with another factor that represented the fiber length influence on beam capacity, as suggested in past research. The comparison between the ultimate moment of the test results and the moment predicted from the modified past research model presented a good correlation.